An improved method for the visualization of conductive vessels in Arabidopsis thaliana inflorescence stems - Jupa, Radek; Didi, Vojtěch; Hejátko, Jan; Gloser, Vít (Frontiers in plant science, 2015)
Dye perfusion is commonly used for the identification of conductive elements important for the study of xylem development as well as precise hydraulic estimations. The tiny size of inflorescence stems, the small amount of vessels in close arrangement, and high hydraulic resistivity delimit the use of the method for quantification of the water conductivity of Arabidopsis thaliana, one of the recently most extensively used plant models. Here, we present an extensive adjustment to the method in order to reliably identify individual functional (conductive) vessels. Segments of inflorescence stems were sealed in silicone tubes to prevent damage and perfused with a dye solution. Our results showed that dyes often used for staining functional xylem elements (safranin, fuchsine, toluidine blue) failed with Arabidopsis. In contrast, Fluorescent Brightener 28 dye solution perfused through segments stained secondary cell walls of functional vessels, which were clearly distinguishable in native cross sections. When compared to identification based on the degree of development of secondary cell walls, identification with the help of dye perfusion revealed a significantly lower number of functional vessels and values of theoretical hydraulic conductivity. We found that lignified but not yet functional vessels form a substantial portion of the xylem in apical and basal segments of Arabidopsis and, thus, significantly affect the analyzed functional parameters of xylem. The presented methodology enables reliable identification of individual functional vessels, allowing thus estimations of hydraulic conductivities to be improved, size distributions and vessel diameters to be refined, and data variability generally to be reduced.
Keywords: fluorescence; Fluorescent Brightener 28; vessel; xylem; dye perfusion; conductive elements; hydraulic conductivity